Pengalaman Keluarga Yang Merawat Anak Penderita Tb Paru - Suci Deni Rekayati; Tri Sakti Widyaningsih; Dwi Nur Aini (Jurnal Keperawatan, 2019)
Pulmonary TB in children is often overlooked or ignored due to symptoms that are not specific in the diagnosis. The purpose of this study was to determine the experience of families caring for children with pulmonary TB in the work area of Lebdosari Community Health Center. Phenomenological approach with taking sampling use purposive sampling of five participants by collecting data through in-depth interviews and field notes. The researcher analyzes the data after and during the research, then to find out the validity of the data using member checking. The parents knew that the child was diagnosed with pulmonary TB from the results of a chest X-ray examination. Feeling sad and distrustful knowing that, when asked parents understand pulmonary TB as a cough, runny nose and fever that does not heal. Efforts include meeting nutritional needs, limiting activities and environmental hygiene. The challenge is when taking medication, the family provides support by assisting in taking the medicine and the parents hope that their child can be completely cured. Children affected by pulmonary TB need proper care include meeting nutritional needs, limiting activities, environmental hygiene and routine treatment, as well as family support needed to overcome obstacles in taking medication during the treatments process.